FDI incentives pay – politically - Nathan M. Jensen; Edmund J. Malesky (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
The authors find that there are strong political benefits to attracting FDI at the state-level in the United States, and that fiscal incentives for attracting such investment, regardless of their effectiveness, may be a strategic political tool for state politicians.
Keywords: 330